Encyclopedia of leadership - Goethals, George R.; Sorenson, Georgia Jones; Burns, James MacGregor; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 2004)
The 'Encyclopedia of Leadership' brings together everything that is known and truly matters abour leadership as part of the human experience.
"A Berkshire Reference work."
"A SAGE reference publication."
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Leadership -- Encyclopedias; Electronic books